Medicare part D prescribing for direct oral anticoagulants in the United States: Cost, use and the "rubber effect". - Panayiotis D Ziakas; Irene S Kourbeti; Loukia S Poulou; Georgios S Vlachogeorgos; Eleftherios Mylonakis (PLoS ONE, 2018)
Introduction Direct oral anticoagulants (DOAC) have gained an increased share over warfarin for prevention and treatment of thromboembolic disease. We studied DOAC adoption across providers and medical specialties. Methods Retrospective, cross-sectional analysis of Medicare Part D public use files (PUF), 2013 to 2015. We summarized prescription data for claims and drug payment, stratified by drug class, specialty and calendar year. We treated DOAC claims as a count outcome and explored patterns of expansion across prescribers via a truncated negative binomial regression. We described dispersion and spread in DOAC prescribing, across hospital referral regions (HRRs), including the p90/p10 ratios, and the median absolute deviation from the median. Results In 2015 part D PUF, oral anticoagulant claims have climbed to approximately 24.4 million with a payment cost of approximately $3.3 billion. DOAC claims comprised 31.0% of oral anticoagulant claims, showing a relative increase of approximately 127% compared to 2013. The upper decile of prescribers accounted for half of the oral anticoagulant prescriptions and the resulting cost. The median cost per DOAC claim in 2015 was $367.4 (interquartile range 323.9 to 445.9), as opposed to $12.3 (interquartile range 9.2 to 16.5) for warfarin. The median cost per standardized (30-day supply) prescription was $317.0 (interquartile range 303.8 to 324.3) and $8.0 (6.7 to 9.8) for DOACs and warfarin, respectively. DOAC adoption differs by specialty. Cardiologists, cardiac electrophysiologists and orthopedics had the highest predicted DOAC share per 100 claims (53.8, 72.9 and 71.5, respectively in 2015); nephrologists, family practitioners and geriatricians the lowest (22.3, 21.5 and 20.7, respectively in 2015). The p90/p10 ratio and the median absolute deviation from the median varied across HRRs and correlated positively with the prevalence of stroke and atrial fibrillation in the Medicare population. Conclusions DOACs have been increasing their share year-over-year, but adoption varies across specialties. In prevalent areas for stroke and atrial fibrillation, prescription dispersion magnifies, and this may signify a rapid adoption by top providers.